Hourglass cystic schwannoma of the trochlear nerve - Bartalena, T.; Leoni, C.; Pastore Trossello et al., M. (Acta Biomedica Atenei Parmensis, 2010)
Cranial nerves’ schwannomas most commonly arise from the vestibular nerve. Involvement of other cranial nerves, in absence of neurofibromatosis, is extremely rare. A case of a pathology proven trochlear nerve schwannoma, with internal cystic components, in a patient with isolated right superior oblique muscle palsy, is described. Only 67 cases of such entity have been previously reported in the literature.